Implementation of Digital Technology in Increasing Transparency and Accountability of Zakat and Tax Management in Madiun City - Ahmad Kudhori; Hendrik Kusbandono; Koerniawan Dwi Wibawa (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study aims to determine the digital technology needed to synergize the zakat database with the tax database, to determine the advantages and disadvantages of implementing technology in managing zakat and tax, and to understand taxpayer awareness when the zakat database can be synergized with the tax database. Zakat and Tax are two different concepts, but along with the development of technology, both use digital technology in carrying out their operational activities. The research method used is a descriptive method with a qualitative approach. The stages in this study are topic selection, research design, data collection using interviews, observations, documentation, data analysis, data validation by triangulating data and the last is writing a report. The results of the study stated that with the implementation of a digital system, data collection and reporting become more efficient, accurate, and easily accessible to the public. This not only strengthens public trust in zakat and tax management institutions, but also increases taxpayer and zakat payer compliance. Although there are challenges such as data security issues, infrastructure limitations, and lack of digital skills among officers and the community, the benefits obtained from implementing this technology are much greater